A synergistic approach to achieving high conduction and stability of CsH2PO4/NaH2PO4/ZrO2 composites for fuel cells. Issue 1 (11th November 2021) - Veer, Dharm; Kumar, Pawan; Singh, Deshraj; Kumar, Devendra; Katiyar, Ram S
Abstract : Solid acid composites of CsH2 PO4 /NaH2 PO4 /ZrO2 with different weight ratios of CsH2 PO4 (CDP), NaH2 PO4 (SDP), and ZrO2 were synthesized and characterized. Abstract : Solid acid composites of CsH2 PO4 /NaH2 PO4 /ZrO2 with different weight ratios of CsH2 PO4 (CDP), NaH2 PO4 (SDP), and ZrO2 were synthesized and characterized. The structure and morphology of the composites were investigated by XRD, FESEM, EDX, and FTIR techniques. The thermal stability and conduction were described for the solid acid composites using TGA, DTA, and conductivity measurements. NaH2 PO4 increased the low-temperature conductivity of CDP by up to 1.5 orders of magnitude and ZrO2 enhanced the conductivity above the transition temperatures. Additionally, the composites showed excellent stability. The superprotonic transition behavior was identified at temperatures from 220 to 270 °C. The conductivity of the composites was examined in air and under confined conditions and also their decomposition was investigated. Our findings suggest that NaH2 PO4 /ZrO2 is an appropriate composite for achieving the high conductivity and stability of CDP.